Evaluation of learning: from measurement to evaluation by competences - La Madrid-Vivar, Pablo L. (2020)
Our objective is to describe the problem of the pedagogical evaluation in the educational centers of the basic level of Peru, which has been confused with the quantitative measurement, evaluating means assigning passing or disapproving grades. Teachers confuse it with the application of written exams in a given period, written exams are rooted in the pedagogical practice of Peruvian teachers, the matter is aggravated because teachers do not use assessment instruments, and above all they persist in their traditional evaluative practice, they do not understand that in the current moments of educational changes, an evaluation by competencies is proposed, which means to vary the classic way of evaluating. The methodology used was bibliographic research, whose support was the theoretical review of texts on educational evaluation. The conclusions we reached were that the evaluation as a training process that aims to improve student learning is not taken into account in the Peruvian educational system. The evaluation implies reflection and analysis of the pedagogical actions carried out during the development of learning in order to correct the weaknesses or enhance the strengths found, however, its relevance, this is ignored. The belief that measuring is evaluating does not help to consolidate the Peruvian evaluative system.